2013
DOI: 10.1364/oe.21.030964
|View full text |Cite
|
Sign up to set email alerts
|

Perfect blackbody radiation from a graphene nanostructure with application to high-temperature spectral emissivity measurements

Abstract: We report the successful fabrication of a novel type of blackbody material based on a graphene nanostructure. We demonstrate that the graphene nanostructure not only shows a low reflectance comparable to that of a carbon nanotube array but also shows an extremely high heat resistance at temperatures greater than 2500 K. The graphene nanostructure, which has an emissivity higher than 0.99 over a wide range of wavelengths, behaves as a standard blackbody material; therefore, the radiation spectrum and the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…However, by using scratch techniques, growth of petals with some degree of alignment can be realized. Also, in recent experiment graphene nanoneedles with a certain degree of alignment were observed after anisotropic hydrogen plasma etching of the carbon substrate [23].…”
Section: Graphitic Gratingsmentioning
confidence: 91%
“…However, by using scratch techniques, growth of petals with some degree of alignment can be realized. Also, in recent experiment graphene nanoneedles with a certain degree of alignment were observed after anisotropic hydrogen plasma etching of the carbon substrate [23].…”
Section: Graphitic Gratingsmentioning
confidence: 91%
“…At this point, we need to consider the emissivity ε e . Matsumoto et al 54 reported the successful fabrication of a type of blackbody material based on a graphene nanostructure and found that the nanostructure exhibited blackbody radiation with emissivity of 0.99 over a wide range of wavelengths. Brar et al 53 studied electronic control of blackbody emission from graphene plasmonic resonators on a silicon nitride substrate and they have shown that graphene resonators produce antenna-coupled blackbody radiation, and manifest as narrow spectral emission peaks in the mid-IR.…”
Section: Efficiency Of Graphene Thermionic Energy Conversion With Lowmentioning
confidence: 99%
“…(13)] would be lowest for ε e ¼ 1 (perfect blackbody) and would be maximum for the lowest value of ε e . In this paper, to study the effect of emissivity on efficiency η of solar TEC, we consider ε e ¼ 1 (perfect blackbody) 54,53 for the values of η in Table 1 and ε e ¼ 0.016 (gray-body emitter) 55,56 for the values of η in Table 2. Comparing the first two rows (Table 1), we see that the efficiency increased from 45.6% to 50% when the emissivity ε s decreased from 1 to 0.08.…”
Section: Efficiency Of Graphene Thermionic Energy Conversion With Lowmentioning
confidence: 99%
“…A good solution here that has been recently explored [10], is to employ graphene filaments as they provide both good emissivity, high temperature throughput and high repeatability [10], [11].…”
Section: A Concept Definitionmentioning
confidence: 99%